Prognostic impact of P53 status, TLS-CHOP fusion transcript structure, and histological grade in myxoid liposarcoma: A molecular and clinicopathologic study of 82 cases - Antonescu, C. R. (Institutional Knowledge at Singapore Management University, 2001)
Purpose: A specific TLS-CHOP fusion gene resulting from the t(12;16) is present in at least 95% of myxoid liposarcomas (MLS). Three common forms of the TLS-CHOP fusion have been described, differing by the presence or absence of TLS exons 6-8 in the fusion product. Type 5-2 (also known as type II) consists of TLS exons 1-5 fused to CHOP exon 2; type 7-2 (also known as type I) also includes TLS exons 6 and 7 in the fusion, whereas type 8-2 (also known as type III) fuses TLS exons 1-8 to CHOP exon 2. We sought to determine the impact of TLS-CHOP fusion transcript structure on clinical outcome in a group of well-characterized MLS cases. We also analyzed P53 status, because this parameter has been found to have a significant prognostic impact in other sarcomas with chromosomal translocations. Methods: We analyzed TLS-CHOP fusion transcripts by reverse-transcription PCR using RNA extracted from frozen tissue in 82 MLS confirmed previously to harbor a CHOP rearrangement either by Southern blotting or by cytogenetic detection of the t(12;16). Parameters analyzed included age, location, size, percentage of round cell (RC) component, areas of increased cellularity, necrosis, and surgical margins. In 71 (87%) cases, adequate tumor tissue was available for immunohistochemical analysis of P53 status, using DO7 antibody. The Kaplan-Meier method, log-rank, and Cox regression tests were used for survival analyses. Results: Most MLS were >10 cm (73%), arising in the thigh (70%), and localized at presentation (89%). RC component was